2015
DOI: 10.1179/1607845415y.0000000048
|View full text |Cite
|
Sign up to set email alerts
|

Association of homocysteine and inflammatory-related molecules in sickle cell anemia

Abstract: Our findings suggest that the increased levels of IL-17,Hcy and sVCAM contributes contributes to the vascular inflammation and activation presented by SCA patients, which probably have an important role in vaso-occlusion. On the basis of the presented data, IL-17 and Hcy might be considered as important components in the pathogenesis of SCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 31 publications
2
16
1
Order By: Relevance
“…There are a few reports in the literature pertaining to the role of IL-12 and IL-17 in SCA [10,69]. Unlike our results, Taylor et al [70] did not observe detectable levels of IL-12 in SCA patients at steady state compared to healthy control subjects; however, as in our study, they observed high levels of IFN-γ.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…There are a few reports in the literature pertaining to the role of IL-12 and IL-17 in SCA [10,69]. Unlike our results, Taylor et al [70] did not observe detectable levels of IL-12 in SCA patients at steady state compared to healthy control subjects; however, as in our study, they observed high levels of IFN-γ.…”
Section: Discussioncontrasting
confidence: 97%
“…The role of IL-17 in SCA are not well understood [69]. Corroborating with our results, Vilas-Boas et al [10] and Pitanga et al [69] observed higher levels of IL-17 in SCA patients at steady state than in healthy donors. Vilas-Boas et al still found a positive association between homocysteine and IL-17 and suggest a possible role of homocysteine in the induction of IL-17.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The immunological aspects of SCD have been widely studied among individuals with sickle cell anemia (SCA), with high levels of cytokines detected, including interleukin (IL) 4, 6, 8, 10, and tumor necrosis factor-alpha (TNF-a) [ 11 ]. In addition, transforming growth factor-beta (TGF- β ) and IL-17 were also found to be associated with vascular activation and inflammation based on a direct association with arginase levels [ 12 ]. Differences were found in the levels of cytokines (IL1 β , IL6, TNF-a, and TGF- β ), lipid inflammatory mediators (LTB4 and PGE2), and modulators of vascular remodeling (MMP9 and TIMP1) between SCA individuals in steady- and crisis-state, permitting the characterization of these two groups using these parameters [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The TGF- β pathway is involved in several cellular processes, since signal transduction involves binding with transforming growth factor- (TGF-) beta receptors (TGF β RI, TGF β RII, or TGF β RIII), which activate mothers against decapentaplegic homolog (SMAD) proteins and other mediators. As TGF- β is known to activate several mediators, the TGF- β pathway is considered to play a role in immune response, angiogenesis, inflammation, hematopoiesis, vascular inflammation, and cell proliferation [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%